(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the surgical outcomes of impacted mandibular third molars using the buccal triangular flap at Vinh Tuong Medical Center in 2023. Methods: A descriptive cross-sectional study was conducted on 30 patients diagnosed with impacted mandibular third molars and treated using the buccal triangular flap technique. Clinical and radiographic characteristics, surgical difficulty levels, and intraoperative and postoperative parameters were collected using a standardized data collection form and analyzed using medical statistical methods. Results: Females accounted for 76.67%, and patients aged over 30 years represented 43.44%. A total of 70% of patients presented with complications. The most common impaction pattern was horizontal (43.33%), with Pell and Gregory class II (50%) and position B (60%). Most cases were classified as difficulty level 2 (56.67%) and level 3 (40%). The mean flap creation time was 20.50 ± 5.6 seconds, suturing time was 3.2 ± 1.5 minutes, and total operative time was 26.27 ± 9.96 minutes. The flap tear rate was 3.33%. At 24 hours postoperatively, moderate pain accounted for 56.67% and severe pain for 23.33%; by day 7, 93.33% of patients reported no pain. Swelling peaked on day 3 (32.84 ± 11.76 mm) and decreased to 4.7 ± 5.9 mm by day 7. Postoperative bleeding occurred in 13.33% immediately after surgery but was not observed after 2 hours. Wound dehiscence occurred in 3.33% of cases. No cases of alveolar osteitis were recorded. Conclusion: Surgical extraction of impacted mandibular third molars using the buccal triangular flap is a safe and effective technique with low complication rates and favorable recovery outcomes, making it suitable for routine clinical practice.